IRF3 Promotes Production of IL-6 and Nitric Oxide but Represses CCL22 in RAW264.7 Macrophage Cells Exposed to Lipopolysaccharides in Culture - Moore TC; Pinkerton TS; Petro TM (Journal of Inflammation Research)
Tyler C Moore,1 Terrence Scott Pinkerton,1 Thomas M Petro2 1Department of Biology, College of Science and Technology, Bellevue University, Bellevue, NE, 68005, USA; 2Department of Oral Biology, University of Nebraska Medical Center, Lincoln, NE, 68583, USACorrespondence: Thomas M Petro, Department of Oral Biology, University of Nebraska Medical Center, College of Dentistry, 4000 East Campus Loop South, Lincoln, NE, 68583, USA, Email tpetro@unmc.eduIntroduction: Macrophage responses to lipopolysaccharides (LPS) drive inflammatory diseases, such as periodontitis, with production of IL-6 and Nitric Oxide (NO). However, anti-inflammatory macrophages counter inflammation with the production of CCL22. Interferon regulatory factor 3 (IRF3) plays a significant role in expression of both IL-6 and NO during macrophage responses through Interferon-stimulated Response Elements (ISREs) of promoters.Methods: To determine the role of IRF3 in LPS-induced pro- and anti-inflammatory macrophage responses, we used the macrophage cell line RAW264.7 modified with an ISRE promoter driving secreted luciferase (RAW264.7-Lucia) to assess IRF3 activity in response to Escherichia coli and Porphyromonas gingivalis LPS. For comparison, responses to poly I:C and IFN-gamma and responses from RAW264.7 cells deficient in IRF3 were also assessed.Results: Herein, LPS of P. gingivalis, significantly enhanced production of IL-6 and NO that was induced by E. coli LPS but significantly decreased poly I:C-induced ISRE promoter activity. Moreover, IRF3 deficiency depressed the LPS-induced ISRE promoter activity and NO production but increased IL-6 and CCL22 in response to LPS. Restoration of IRF3 expression in IRF3KO RAW cells increased IL-6, restored NO, and decreased CCL22 production in response to LPS of E. coli.Discussion: Therefore, IRF3 is critical to the expression of pro- and anti-inflammatory factors produced by macrophages responding to LPS and could be a target during periodontitis treatment.Keywords: IRF3, lipopolysaccharide, macrophages, RAW264.7 cells, cytokines